2017
DOI: 10.1159/000466682
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Five-Year Changes in the Levels of N-Terminal Fragment of the Prohormone Brain-Type Natriuretic Peptide (NT-proBNP) with Subsequent Heart Failure and Death in Patients with Stable Coronary Artery Disease: The Heart and Soul Study

Abstract: Background: The N-terminal fragment of the prohormone brain-type natriuretic peptide (NT-proBNP) is a powerful predictor of adverse outcomes in patients with coronary artery disease (CAD). However, little is known regarding the prognostic significance of longitudinal changes in NT-proBNP levels. Methods: We evaluated the ability of 5-year changes in NT-proBNP levels to predict subsequent heart failure (HF) hospitalization or cardiovascular (CV) death in 635 participants with stable CAD enrolled in the Heart an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…Investigators from the Heart and Soul Study have reported that among patients with stable CVD, an increase of NT-proBNP was an independent predictor of subsequent HF and CV death over a long period of time. 25 These previous results are consistent with our findings, given the known association between HF and AF, through common risk factors and as causes of each other. 26, 27 Though not directly relevant, repeated measurements of NT-proBNP might provide predictive information on the risk of cardiovascular mortality among persons with AF.…”
Section: Discussionsupporting
confidence: 93%
“…Investigators from the Heart and Soul Study have reported that among patients with stable CVD, an increase of NT-proBNP was an independent predictor of subsequent HF and CV death over a long period of time. 25 These previous results are consistent with our findings, given the known association between HF and AF, through common risk factors and as causes of each other. 26, 27 Though not directly relevant, repeated measurements of NT-proBNP might provide predictive information on the risk of cardiovascular mortality among persons with AF.…”
Section: Discussionsupporting
confidence: 93%
“… 86 , 87 High levels of NT-proBNP are associated with vulnerable plaque components 88 and have been shown to predict outcome in patients with coronary heart disease and patients who experienced an ischemic stroke. 89 , 90 In PAD patients, similar results have been published with a strong association between all-cause mortality and increased NT-proBNP levels. The association with MACE and NT-proBNP is less frequently studied but also showed a moderately increased risk.…”
Section: Discussionsupporting
confidence: 53%
“…NT-proBNP is a cleavage product of proBNP that is released by the myocardium in response to left ventricular wall stress [18,19]. In patients with stable coronary artery disease, relevant coronary stenosis may cause transient myocardial ischemia, thereby probably increasing wall stress and releasing natriuretic peptides [20].…”
Section: Pathophysiologic Considerationsmentioning
confidence: 99%